Gómez Jene, Miguel, International Commercial Arbitration in Spain - Calvo Caravaca, Alfonso-Luis (CUADERNOS DE DERECHO TRANSNACIONAL, 2020)
This article reviews: Gómez Jene, Miguel, International Commercial Arbitration in Spain, Wolters Kluwer International, The Netherlands, 2019, 380 pp.